Lessons about national identity: post-war reflections of therapist and researchers from the former Yugoslavia - Rolovic, Jelisaveta-Sanja; Čorkalo Biruški, Dinka; Shanini, Mimoza; Kukic, Sandra (2011)
Critical lessons can be learned from how citizens struggle to clarify their multiple relationships to country, community, ethnic/national identity, family and self in postwar societies. Therapists and researchers from Croatia, Kosovo, Bosnia and Herzegovina and Serbia will explore how transformations in the meanings of ethnic/national identity have affected their professional work and everyday lives. How feelings about one’s country and ethnic identity facilitates or interferes with clinical and research work on individual and collective trauma will be analyzed using research data from the region and personal and clinical examples. Links between issues of human rights and national/ethnic identity in the region of the former Yugoslavia will be discussed. Emphasis will be given to the roles professionals can play in the healing processes of the individuals and the communities and to the intra- and interpersonal world of the therapist exposed to suffering caused by war trauma. Lessons learned while working in divided communities will be highlighted in order to outline guidelines for both clinical work and research practice in situations of "competing identities".
12th European Conference on Traumatic Stress (12.-15.6.2011. ; Beč, Austrija)
Projekt MZOS
ENG